أثر التمويل الزراعي التقليدي و الإسلامي في التنمية الزراعية الاقتصادية - لمحنط عائشة (جامعة الوادي - University of Eloued, 2020)
هـدفت هــذه الدراسـة إلى قيــاس وتحليــل أثـر التمويــل الزراعـي في التنميــة الزراعيــة الاقتصـادية، كمــا ســعت إلى التمييز بين أثر كلا من التمويل الزراعي التقليدي والإسلامي في التنمية الزراعية من خلال المقارنـة بـين حالـة الجزائـر ذي النظام المصرفي التقليدي، وحالة السودان ذي النظام المصرفي الإسلامي. وتم اسـتخدام نمـوذج الانحـدار الـذاتي ذو الفجـوات الزمنيـة الموزعـة (ARDL (للفـترة (2016-1995)، كمـا تم اختيار أربعة مؤشرات اقتصادية للتنمية الزراعية كمتغيرات تابعة وهي: الناتج الزراعي، الصادرات الزراعية، الواردات الزراعيـة والفجــوة الغذائيــة، وتم بنــاء نمـوذج لكــل متغــير تــابع في كــل مـن الــدولتين، بالإضــافة إلى اختيــار متغــيرات مستقلة خاصة بكل نموذج من أهمها التمويل المصرفي الزراعي، الميكنة الزراعيـة، العمالـة الزراعيـة، سـعر الصـرف، في كل من الدولتين محل الدراسة وذلك لقياس أثر التمويل المصرفي الزراعي في التنمية الزراعية كمتغير تابع. ومن أهم ما توصلت إليه الدراسة أنه في الجزائر لم تكن القروض الزراعية أداة فعالة لتعزيز التنمية الزراعية. بينما في السـودان، كـان للتمويـل الزراعـي أثـر معنـوي علـى كـل مـن النـاتج الزراعـي والصـادرات الزراعيـة، في حـين لم يكـن التمويل المصرفي للقطاع الزراعي أداة فعالة لتخفيض الـواردات الزراعيـة والفجـوة الغذائيـة. كمـا توصـلت الدراسـة إلى أن هناك أفضلية نسبية للتمويل الزراعي الإسلامي في تعزيز التنمية الزراعية مقارنة بالتمويل الزراعي التقليدي وذلك على مستوى زيادة كل من الناتج الزراعي والصادرات الزراعية. This study aimed to reveal the impact of the agricultural financing on the economic agricultural development. Moreover, it sought to distinguish between the effect of the conventional and Islamic agricultural financing on the agricultural development by the comparison between Algeria with the conventional banking system, and the Sudan with the Islamic one. In attempt to accomplish its objectives, this study incorporated the Autoregressive Distributed Lags (ARDL) modeling for the period (1995-2016. It also selected four economic indicators as dependent variables. These include مــلخـص the agricultural product, the agricultural exports, the agricultural imports and the food gap. Additionally, the study framed a model for each dependent variable in each of the two states. Furthermore, for each specific model, this research selected relevant independent variables, amongst which the agricultural bank financing, the agricultural mechanization, the agricultural labour, the exchange rate in both states under investigation for the purpose of measuring the effect of the agricultural bank financing on the agricultural development as a dependent variable. The most important findings of the study revealed that the agricultural loans had not been an effective tool to enhance the agricultural development in Algeria. Whereas in the Sudan, the agricultural finance had a significant impact on both the agricultural product and the agricultural exports. Conversely, the banking finance of the agricultural sector has not been effective to reduce either the agricultural imports or the food gap in the Sudan. The study also concluded that there had been a relative priority for the Islamic agricultural finance compared to the conventional one in boosting the economic agricultural development, at the level of increasing the agricultural product as well as the agricultural exports.
2016دراسة مقارنة بين الجزائر و السودان للفترة من 1995 إلى
أطروحة دكتوراه تخصص تحليل اقتصادي في العلوم الاقتصادية و التجارية و علم التسيير
Keywords: تمويل زراعي؛ تمويل مصرفي تقليدي؛ تمويل مصرفي إسلامي؛ تنمية الزراعية.; agricultural finance; conventional finance; Islamic finance; agricultural development.